The Influence of the Use of Electronic Medical Record Systems on Effective Doctor-Patient Communication Relationships in the Outpatient Clinic - Lestari, Nadia Putri; Ramadhani, Isniani; NurCita, Boenga; Kristanti, Melly (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Electronic medical records are being used based on the Regulation of the Minister of Health (PMK) number 24 of 2022 concerning Medical Records, which is a transition of patient medical records from conventional systems to electronic-based. This study aims to determine the effect of using an electronic medical record system on effective doctor-patient communication relationships in hospital outpatient clinics. This study was conducted at a B-class general hospital in Jakarta Regional General Hospital, using an analytical descriptive method and a cross-sectional approach. A total of 153 respondents followed quota sampling rules. The test used was the chi-square test, with the p-value being less than 0.05. Approximately 50% of respondents demonstrated high levels of effective doctor-patient communication and high levels of knowledge on the use of RME. This study states that there is a positive relationship between the use of electronic medical records and effective communication between doctors and patients.